Sensitive Determination of Cetirizine Using CdS Quantum dots as Oxidase Mimic-mediated Chemiluminescence of Sulfite - Kouhestany, Reza Hoseinpour; Azizi, Seyed Naser; Shakeri, Parmis; Rahmani, Shaghyegh (International Current Pharmaceutical Journal, 2016)
A new chemiluminescence (CL) method using cadmium sulfide quantum dots (QDs) as sensitizers is proposed for the chemiluminometric determination of cetirizine pharmaceutical formulation. CdS QDs were synthesized by using water soluble route. The nanoparticles were structurally and optically characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Ultra Violet-Visible (UVVis) absorption spectroscopy and scanning electron microscopy (SEM). In this study results shows that CdS quantum dots are enhancers of the weak CL emission. Trace amounts of cetirizine improved the sensitize effect of CdS quantum dots yielding a significant chemiluminescence enhancement of the Ce(IV)SO32?CdS QDs system. So, a new CL analysis system was selected for the determination of cetirizine. There is a good linear relationship between the relative chemiluminescence intensity and the concentration of cetirizine in the range of 1×10?9 1×10?6 molL?1 with a correlation coefficient (R2) of 0.9963 at the optimum conditions. The limit of detection (LOD) of this system was found to be 5×10?11 M. This method is simple, sensitive and cost effective, and also is accommodating for pharmaceutical applications. Kouhestany et al., International Current Pharmaceutical Journal, June 2016, 5(7): 59-62